Girls get smart, boys get smug: Historical changes in gender differences in math, literacy, and academic social comparison and achievement. (April 2018) - Parker, Philip D.; Van Zanden, Brooke; Parker, Rhiannon B.
Abstract: Girls' lack of self-belief has frequently been cited as a major barrier to advancement in both empirical research and in the popular imagination. With girls now outcompeting boys at almost every educational level, this paper considers if girls still have lower self-concept than boys, if this changes when controlling for academic ability, and what mechanisms explain gender differences. We compare and contrast rational choice, contrast, and assimilation approaches to self-concept and juxtapose historical trajectories in gender differences in self-concept and achievement to distinguish between them. We do this in five age cohorts born between 1981 and 1993 (N = 66, 522) for math, literacy, and general academic domains. Results suggest that there are still significant differences in self-concept between equally able boys and girls and that a mix of assimilation and contrast mechanisms likely explains the size and direction of these effects. Highlights: Girls have closed the gap in math with boys and have extended their led in literacy. Yet boys have more positive academic self-beliefs when controlling for ability. We aim to explain this via social comparison and stereotype processes. Analysis of archival data show a complex array of gendered processes at work.